Skill Development and Employment Opportunities in Food Processing Industry : A Futuristic Perspective (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2022)
With an annual growth rate of 7.2%, India has become one of the world's fastest expanding economies. India is one of the world's top producers of rice, wheat, milk, lentils, and a range of fruits and vegetables, and the food processing sector of the country has greatlycontributed to the Indian GDP growth. The food processing sector now facing tremendous industrial changes and embracing automation, mechanisation, and technology to maximise the productivity. The evolution of the industry necessitates the acquisition of a variety of technical and specialised abilities. The food processing industry is expected to add 44.34 lakh new jobs by 2022, primarily in entry-level and managerial positions. However, as a result of the industrial revolution, the food processing business will face significantchallenges. Approximately 44% of the workforce is employed in the agri-foods processing sector, with the majority of workers lacking any formal or informal skill training causing underutilization of the human resources. There lies the real challenge as well as theopportunity in the food processing industry to skill newcomers and upskill or reskill the existing workforces. NSDC reports a huge skill gap in various sectors of Indian food processing industry. The skill gaps must be addressed to meet the industry skills needs andto harness the maximum potential of the food processing sector. In response to the need for skilled labour and realizing the importance of the food processing industry in the country's development, The Government of India (GOI) is taking major initiatives such as Aatmanirbhar Bharat, Skill India Mission, National Education Policy 2020. The presentreview paper attempts to discuss skill development and employment opportunities in food processing industry in India.